2003
DOI: 10.1108/02630800310479098
|View full text |Cite
|
Sign up to set email alerts
|

Fibre reinforced polymer materials for prestressed concrete structures

Abstract: Fibre reinforced polymer (FRP) materials are currently used for concrete structures in areas where corrosion problems are serious. Recent applications of FRP rebars in normal reinforced concrete structures in fact cannot fully utilise the strength of FRP. A more rational use of FRP would be in the area of prestressed concrete (PC) structures. In spite of the superb strength provision of FRP tendons over steel tendons, use of FRP PC members is often questioned by practising design engineers. This is largely due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The use of fibre-reinforced polymer (FRP) plates in strengthening damaged structures offers an effective and rapid repair solution. This has made bonding an excellent alternative for conventional reinforcing techniques such as welding, riveting, bolting, etc., due to their excellent material properties in terms of strength-to-mass ratio, environment resistance and cost effectiveness (Balendran et al, 2001;Leung et al, 2003). The studies of Moy and Nikoukar (2002) and Tavakkolizadeh and Saadatmanesh (2003) confirmed the efficiency of this strengthening technique.…”
Section: Introductionmentioning
confidence: 64%
“…The use of fibre-reinforced polymer (FRP) plates in strengthening damaged structures offers an effective and rapid repair solution. This has made bonding an excellent alternative for conventional reinforcing techniques such as welding, riveting, bolting, etc., due to their excellent material properties in terms of strength-to-mass ratio, environment resistance and cost effectiveness (Balendran et al, 2001;Leung et al, 2003). The studies of Moy and Nikoukar (2002) and Tavakkolizadeh and Saadatmanesh (2003) confirmed the efficiency of this strengthening technique.…”
Section: Introductionmentioning
confidence: 64%
“…This implies that both elastic and long-term pre-stressing losses occurring in pre-stressed concrete elements due to the shortening of the member could be relevantly reduced. Composite reinforcement as a pre-stressing material was investigated by Nanni and Tanigaki [10], Leung et al [11], Lees and Burgoyne [12] (aramid), Stoll et al [13] and Du et al [14] (carbon), Atutis et al [15] (glass) and Crossett et al [9] (basalt). Zheng et al [16] and Li et al [17] studied the application of carbon composite bars as unbonded external post-tensioning reinforcement in concrete structures, whereas their application to post-tension timber structural elements was experimentally investigated by McConnell et al [18].…”
Section: Introductionmentioning
confidence: 99%